THE ROLE OF AEROBIC GYSTERN IN CONTROLLING BLOOD PRESSURE FOR HYPERTENSION PATIENTS - Sriyono, Grido Handoko; Hamim, Nur (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. One of the good physical activities to improve physical fitness is aerobic exercise. Someone who does not have the habit of aerobic exercise have 30-50% tendency in hypertension. Regular aerobic exercise can lower the blood pressure effectively. Physical activity with aerobic exercise is recommended for 30 minutes/day with 3 days/week. This research aimed to determine correlation between aerobic exercise habits and blood pressure in hypertension patients. Methods. This research was descriptive correlative with cross sectional approach. The population was 120 respondents and a sample of 60 respondents at Karangperanti, using purposive sampling technique and data collection using non-standard questionnaires through bivariate data analysis with Pearson Correlation. Results & Analysis. The habit of regular aerobic exercise activities were 32 respondents (52.8%) and irregular activity were 28 respondents (47.2%). The frequency based on respondent's blood pressure showed that SBP had a median value of 150 mmHg, a minimum value of 140 mmHg and a maximum value of 185 mmHg with an average value of 152.55 mmHg and a standard deviation of 11.814 mmHg. Meanwhile, DBP has a median value of 92 mmHg, a minimum value of 90 mmHg and a maximum value of 120 mmHg with a standard deviation of 5.155 mmHg. There is a correlation between aerobic exercise habits and blood pressure in hypertension patient at Karangperanti Village with p value 0.000 (α = 0.05). Discussion. It is expected that people with hypertension always do aerobic exercise with 3 times with a duration of 30 minutes per week.